Analysis of Fraud Heptagon Theory on the Tendency of Fraud in Village Credit Institutions (Pusat Riset dan Inovasi Nasional, 2026)
The tendency of fraud is an unlawful act committed to gain personal or group benefits. Fraud cases that occurred in the Village Credit Institutions (Lembaga Perkreditan Desa/LPD) in Klungkung Regency indicate weak supervision and governance. Based on the Fraud Heptagon Theory, the tendency of fraud is affected by seven factors, namely pressure, opportunity, rationalization, competence, arrogance, culture, and religiosity. This study aims to analyze the effect of pressure, opportunity, rationalization, competence, arrogance, culture, and religiosity on the tendency of fraud. This research employs a quantitative approach with 115 respondents from 64 active LPDs in the mainland area of Klungkung Regency, determined through purposive sampling. Data were collected using questionnaires and analyzed through the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the assistance of SmartPLS 4. The results show that pressure, opportunity, rationalization, competence, and arrogance have a positive effect on the tendency of fraud, while culture and religiosity have a negative effect on the tendency of fraud. The implications of this study can serve as a consideration for LPDs and traditional communities to strengthen supervisory systems, enhance ethics, and instill cultural and religious values to reduce the tendency of fraud.